MULTICULTURAL VALUES IN DISNEY ANIMATED FILMS - Rudy, Rudy; Simanjuntak, Felix Immanuel; Simanjuntak, Zetro Panigoro (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This qualitative research focuses on the discussion of multiculturalism which is essential to do because in the current digital era, people are increasingly active moving from one place to another. Consequently, more and more countries are inhabited by people from different kinds of ethnic groups, cultures, races, etc. and multicultural values are indeed necessary to be applied. As the issue of cultural diversity has been broadly discussed, it is also found in Disney animated films. This study applied the semiotic approach to analyze data in the forms of dialogs as well as scene images obtained from the observation of Disney animated films. The results of study suggested that multicultural values can refer to respect and peace which play an essential role in multicultural society. The study also revealed that the observed animated films could represent multiculturalism through the portraits of animated film characters, traditions and customs as well as philosophy from different cultures. Keywords: multicultural values, multiculturalism, Disney animated films, cultural diversity